Computing Endolymph Hydrodynamics During Head Impulse Test on Normal and Hydropic Vestibular Labyrinth Models - Rey-Martinez, Jorge; Altuna, Xabier; Cheng, Kai; Burgess, Ann M.; Curthoys, Ian S. (Frontiers in Neurology, 2020)
Hypothesis Build a biologic geometry based computational model to test the hypothesis that, in some circumstances, endolymphatic hydrops can mechanically cause enhanced eye velocity responses during clinical conditions of the head impulse test. Background Some recent clinical and experimental findings had suggested that enhanced eye velocity responses measured with the video head impulse test could not only be caused by recording artifacts or central disfunction but also could be directly caused by the mechanical effect of endolymphatic hydrops on horizontal semicircular canal receptor. Methods Data from clinical video head impulse test was computed in three biologic-based geometry models governed by Navier-Stokes equations; six head impulses of incrementally increasing peak head velocity were computed in each one of the three different geometric models, depending on absence, canal or utricular hydrops. Results For all computed head impulses an increased endolymphatic pressure was measured at the ampullar region of the horizontal semicircular canal on both canal and utricular hydrops models. The mean of aVOR gain was 1.01 ± 0.008 for the no-hydrops model, 1.14 ± 0.010 for the canal hydrops model was, and 1.10 ± 0.007 for the utricular hydrops model. Conclusion The results of the physical computation models support-the hypothesis that in endolymphatic hydrops conditions, which are affecting horizontal semicircular canal and utricular region on moderate dilatations, the eye velocity responses output-by the aVOR will be enhanced by a 1.14 factor and aVOR gain values will be enhanced by over 1.1 for impulses to the right side.